MULTI-INFARCT DEMENTIA - Ayu Diandra Sari; Nyoman Ratep; Bagus Komang Satriyasa (Faculty of Medicine, Udayana University, 2013)
Dementia is a cognitive functional deficits that causes memory impairment with symptoms such as: aphasia, agnosia, apraxia or a disturbance in executive functioning (the ability to plan, sequence, and organize) that interferes with social, occupational, or interpersonal skills. Most of dementia among older people in Asia, especially Indonesia is Vascular dementia. Most of vascular dementia among older people in Indonesia is multi-infarct dementia (MID). Multi-infarct dementia (MID) is a disorder involving deterioration in mental function caused by changes or damage to the brain tissues from lack of oxygen as a result of multiple blood clots throughout the brain. Risk factor for MID include a history of: Hardening of arteries (arthrosclerosis), high blood pressure (hypertension), smoking, and stroke. In MID, disruption of blood flow leads to damaged brain tissue. For diagnose the patient with MID, the most important thing we must do is anamnesis. From anamnesis, we can get history of sufficient exposure, Onset of symptoms, checking sign and doing tests, and also ask whether the patient has risks factors about MID or not. There is no known definitive treatment for MID. Treatment is based on control of symptoms. Other treatments may be advised based on the individual condition.